THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY IN IMPROVING THE QUALITY OF LEARNING MANAGEMENT IN THE DIGITAL ERA - Hermawan, Wawan; Endrawati, Eli; Nuarida, Eva Bella (JCI Publisher, 2025)
The digital technology revolution has catalyzed a fundamental paradigmatic transformation in the global education ecosystem, creating a new era where technology integration has become a strategic imperative in effective and sustainable learning management. One of the most disruptive technological innovations that has become the primary focus in educational transformation is Artificial Intelligence (AI), which has demonstrated extraordinary potential in revolutionizing various aspects of learning management through sophisticated adaptive capabilities, deep learning personalization, and comprehensive administrative automation. This research aims to comprehensively and systematically examine the multidimensional role of AI in enhancing the quality of learning management in the digital era, with in-depth analytical focus on three fundamental pillars: strategic learning planning, pedagogical process implementation, and learning outcome evaluation. The research methodology employs a rigorous Systematic Literature Review (SLR) approach, analyzing over 150 high-quality scientific articles from leading national and international journals published between 2014-2024, utilizing a thematic synthesis framework to identify emergent patterns and significant trends in AI implementation in education. Research findings reveal that AI implementation in learning management produces multifaceted transformative impacts, including significant improvements in pedagogical decision-making quality through predictive analytics and data-driven insights, strengthening the strategic role of teachers as adaptive and responsive learning facilitators, and expanding democratic learning accessibility through adaptive learning systems and intelligent tutoring systems technologies. AI has also proven effective in optimizing educational resource allocation, enhancing student engagement through intelligent gamification, and facilitating inclusive and equitable learning. However, this research also identifies complex challenges that must be addressed in AI implementation, including significant technological infrastructure gaps particularly in remote areas, limitations in educators' digital literacy affecting technology adoption, and ethics and data privacy issues requiring comprehensive regulatory frameworks. The implications of this research emphasize the need for a holistic and structured approach in integrating AI into educational systems, considering technological, pedagogical, and socio-cultural aspects in a balanced manner to achieve sustainable and positively impactful educational transformation.